Desperately Seeking (Environmental) Kuznets - Marzio Galeotti; Alessandro Lanza (Fondazione Eni Enrico Mattei (FEEM), 1999)
The number of studies seeking to empirically characterize the reduced-form relationship between a country's economic growth and the quantity of various pollutants produced has recently increased significantly. In several cases researchers have found evidence in favor of an inverted-U "environmental Kuznets" curve. In the case of a major greenhouse gas, CO2, however, the evidence is at best mixed. This paper attempts to shed further light on this issue by using a newly developed data set covering over one hundred countries around the world for the last twenty five years and by considering alternative functional forms together with an effort to rigorously discriminate among competing alternatives.
Keywords: O13; Q30; Q32; C12; C23; 330; Environment; Growth; CO2 emissions; Panel data; Wirtschaftswachstum; Umweltbelastung; Treibhausgas-Emissionen; Schätzung; Welt; Environmental Kuznets Curve